Setrategi Masyarakat Desa dalam Menumbuhkan dan Menjaga Nilai Toleransi - Akhirin, Fauzi; Bagaswati, Fatimah Shofia; Kurniawan, Fauzi Indra; Wibowo, Faris Fatah; Lukmana, Defi Intan (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Policies on religious tolerance in Indonesia make it challenging to maintain social harmony due to the variety of cultures and religions. This community service was carried out in Dukuh Tegalsari, Musuk Village, Boyolali Regency, which demonstrates pluralistic harmony but still encounters issues with establishing places of worship. The objective is to discover strategies that rural communities use to foster and preserve tolerance, while providing guidance for local policies. Qualitative methods involved interviewing community members, organizing socialization activities, and executing them to improve awareness of tolerance. Findings emphasize successful strategies, including interfaith dialogue, inclusive education rooted in Pancasila, and shared social events that reinforce community connections. Major obstacles include misunderstandings of religious teachings and harmful stereotypes, which are tackled through education and inclusive government policies. Ultimately, the conclusion highlights that practicing tolerance daily supports lasting social development, positioning Dukuh Tegalsari as an example model for tolerance strategies across Indonesia.